Comparison of mid-term outcomes between unilateral biportal endoscopic and minimally invasive transforaminal lumbar interbody fusion in the treatment of single-level lumbar degenerative disease - Xuelei Zhang; Qiumei Yuan; Yu Zhang; Zuchao Gu; Guo Li (PLoS ONE, 2025)
Objective To compare the mid-term clinical and radiological outcomes between unilateral biportal endoscopic transforaminal lumbar interbody fusion (ULIF) and minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) in the treatment of single-segment lumbar degenerative disease. Methods Patients with L4–S1 disease treated with fusion surgery in our department between August 1, 2019 and June 30, 2020 were retrospectively analyzed. The patients were categorized into ULIF and MIS-TLIF groups based on the surgical method performed. The preoperative demographic baseline and operation-related indicators of the groups were compared, including operative time, estimated blood loss (EBL), postoperative drainage volume, time to ambulation, and postoperative hospital stay. The Visual Analog Scale (VAS) was utilized to assess the severity of back pain (VAS-B) and leg pain (VAS-L). The Oswestry Disability Index (ODI) and Japanese Orthopedic Association (JOA) scores were employed to evaluate the level of functionality. Bridwell criteria were used to evaluate interbody fusion. The lumbar lordotic angle (LLA), intervertebral disc height (IDH), and segmental lordotic angle (SLA) pre- and post-operatively were compared. The creatine kinase (CK), C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), and interleukin-6 (IL-6) levels pre- and post-operatively, and the complication rates were compared. Results The baseline preoperative demographics of the ULIF (n=35) and MIS-TLIF (n=42) groups did not differ significantly. Compared with MIS-TLIF, ULIF had lower intraoperative blood loss and postoperative drainage volume and shorter time to ambulation and postoperative hospital stay, but longer operative time. The VAS-B, VAS-L, JOA, and ODI scores of both groups significantly improved. The VAS-L at 1 week postoperatively, the VAS-B at 1 week and 1 month postoperatively, and the JOA and ODI scores at 1 month postoperatively were better in the ULIF group. At 1 and 3 days postoperatively, the ULIF group exhibited substantially reduced levels of CRP, CK, and IL-6. The fusion rates did not differ significantly at 1 year, 2 years, and 3 years of follow-up. The IDH, SLA, and LLA improved significantly in both groups but no significant differences were observed between the two groups. Complication rates were comparable between the two groups. Conclusions Both ULIF and MIS-TLIF are proven to be safe and effective minimally invasive lumbar fusion techniques. Both achieve comparable outcomes in terms of interbody fusion rate, long-term pain relief, functional improvement, and complication rate. Compared with MIS-TLIF, ULIF has less intraoperative blood loss, less postoperative drainage volume, reduced inflammatory reaction, and faster postoperative pain relief and functional improvement.